Factors associated with stunted growth in children below 11 years of agein Antioquia, Colombia (2004)
ABSTRACT: Objective: To explore some factors associated to stunted growth in children below 11 years of age in the Department of Antioquia. Methodology: Cross-sectional study using the databases of alimentary and nutritional profiles in homes of Antioquia in 2004, based on a representative random sample of homes in the department (95% reliability and error margin of 3%). For this study, 100% of the records of children below 11 years of age were used. A model of generalized equations estimation was constructed for stunted growth classified by a Z score smaller than -2 standard deviation with respect to p 50 of the 1978 NCHS (Centro Nacional de Estadísticas de la Salud - National Center for Health Statistics). Data were analyzed using the GLIMMIX Procedure: SAS version 9.1. Results: We found 18.6% of the children with stunted growth, 75% of the homes with male head of household, 70% of heads of household with maximum 5 years of schooling; 47% of homes were nucleated bi-parental, and 40% extensive with a 5-member median per home; 56.4% poor per unsatisfied basic needs, and 80% in alimentary insecurity. The factors associated to stunted growth were: female gender, 1-5 years of age, head of household with less than 6 years of schooling, more than 5 people in the home, more than two household members under 7 years of age, coming from a poor home per unsatisfied basic needs, belonging to a sub-region different from Medellin, food availability of less than 30 different foods per week, no production of food, and head of household under 40 years of age. Conclusions: Here in, we show evidence of the magnitude of poverty and association of precarious socioeconomic conditions with stunted growth in Antioquia. The study shows the importance of considering the correlated nature of the data for the construction of the model.